Geographic Inequalities in the Distribution of Dentists: A scoping review - Zahra Zare; Erfan Kharazmi; Mohsen Khosravi; Khalil Kalavani (ACHSM, 2024)
Background: Equity in health refers to ensuring that individuals have timely and sufficient access to healthcare services when needed. Human resources are a vital component of healthcare organizations, and they play a crucial role in improving people's access to services. Dentists, in particular, are essential healthcare professionals as oral and dental health significantly impacts overall societal health. This study aims to investigate the key factors contributing to the inequality in the distribution of dentists. Methods: A scoping review was conducted, systematically searching three databases-Scopus, PubMed, and WOS-using relevant keywords until January, 2023. A total of 565 preliminary results were screened, and 447 titles and abstracts were reviewed. Ultimately, 23 full-text articles were included in the analysis. Qualitative content analysis and thematic network were used to synthesize the extracted data. Results: Thematic analysis of the evidence yielded four main themes that contribute to inequality in the distribution of dentists: the development of the inequality situation, methods for analyzing inequality, causes of inequality, and potential solutions to address inequality. Conclusion: Policymakers should gain an understanding of the determinants that contribute to inequality and how these factors manifest in their respective countries. Policymakers can work towards achieving a more equitable distribution of dentists by directing resources towards policies and measures that improve access to oral and dental services. This will ultimately enhance overall societal access to oral healthcare services.